A Qualitative Analysis of Emotional Facilitators in Exercise - Wienke, Benjamin; Jekauc, Darko (Frontiers in Psychology, 2016)
Although previous research has shown that affective variables are consistently associated with physical activity behavior, the working mechanisms are not understood to the extent of creating an intervention. The aim of this study is to identify situations and aspects of physical activity, which lead to positive affective reactions in people taking part in regular and long-term exercise. In this study 24 adults (12 female, 12 male) distributed over three age groups (young, middle, and late adulthood) that took part in sport programs (individual or team sport) for at least five years. Semi-structured in depth interviews with questions about physical activity, long term participation and affective response in a sporting environment were conducted in order to ascertain those situations and aspects of the exercise program triggering positive affective states. Interviews were transcribed verbatim and followed Grounded Theory principles. Emerging concepts were grouped and merged into different categories representing the key aspects of exercise. Four factors were identified which are associated with emergence of positive emotions in sport and exercise. Firstly, perceived competence is one of the major factors influencing affective states during physical activity representing individual and collective success and progress, competition and challenge. Secondly, perceived social interaction is another factor comprising of all sorts of peer-related aspects such as communication with others, being part of a group and creating close relationships or friendships. Thirdly, novelty experience in contrast to other none-sporting activities such as work, family or other leisure activities was another factor. The last factor found was the perceived physical exertion comprising the degree of exhaustion, a possibly delayed turnaround in the affective response and the aspect of sport being a physical compensation for everyday sedentary life. The results of this study provide the starting point for the development of interventions aiming at the promotion of positive affective states in sports in order to increase maintenance and adherence to exercise. Future steps will be the development of a sports program based on this strategy and to test its validity.